Market acceptance of new formulated Sundanese Nasi Liwet: How branding affecting selling of traditional culinary - Dimas Pinandoyo; M.U.C Afriasih; Muhamad Ridwan; Sucheta Khubber (Hasanuddin University Food Science and Technology Study Program, 2023)
This research aimed to analyze the effectiveness of new formulated Sundanese Nasi Liwet. Six new formulated Nasi Liwet had been formulated with the innovation of color and condiments. Overall acceptability was conducted. The six new formulated was sold with a different brand, namely “Milwet” with banana tree nuance, “Liwet Kuy” with mega mendung pattern, “Ngeliwet Yuk” with reddish simplicity nuance, “Ngeliwet” with reddish typography emphasis, “Pawon Indung” with Sundanese traditional jug icon, and “Ini Nasi Liwet” with simple blue nuance. It was found that market acceptance differed with overall acceptability. Despite of lowest overall acceptability, “Milwet” performed the highest market acceptance, followed “Ini Nasi Liwet”, “Ngeliwet”, “Liwet Kuy”, and “Pawon Indung”. Applying good brands could be used as an alternative to popularize traditional culinary.